2010
DOI: 10.1007/s10554-010-9730-0
|View full text |Cite
|
Sign up to set email alerts
|

The presence, characterization and prognosis of coronary plaques among patients with zero coronary calcium scores

Abstract: Patients with coronary artery calcium (CAC) scores of zero are generally considered not to have atherosclerosis. Recent studies involving computed tomography coronary angiography (CTCA) challenge this assumption. This goal of the present study is to assess the frequency, morphology, location, and the prognosis of patients with plaque detected on CTCA and zero CAC. 1,119 patients (51 ± 12 years, 52% male) with a zero CAC score during CTCA study were retrospectively identified. The CTCA studies were assessed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 17 publications
(20 reference statements)
1
20
0
Order By: Relevance
“…Ergün et al reported that age and DM are associated with positive CTCA findings [14]. Uretsky et al reported that age (>60 years), male gender and a current smoking history are associated with a greater tendency to have coronary plaque [15]. Chen et al reported that age (>55 years) and BMI (>27) are independent factors associated with the presence of plaques [18].…”
Section: Discussionmentioning
confidence: 99%
“…Ergün et al reported that age and DM are associated with positive CTCA findings [14]. Uretsky et al reported that age (>60 years), male gender and a current smoking history are associated with a greater tendency to have coronary plaque [15]. Chen et al reported that age (>55 years) and BMI (>27) are independent factors associated with the presence of plaques [18].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Budoff et al (11) reported that the prevalence of acute coronary syndrome was 0.4% in a patient population that was comprised of 25 253 cases with a CAC score of zero over a 12-year follow-up period. During a three-year follow-up of cases with a CAC score of zero, Uretsky et al (18) reported a mortality rate of 0.4%, and the deaths occurred among cases without plaques detected in coronary CT angiography. In 2010, Russo et al (5) found that the occurrence of cardiovascular events in cases with noncalcified or mixed type plaques was higher compared with cases that had a CAC score above 400.…”
Section: Discussionmentioning
confidence: 99%
“…Nikolaou et al (12) found that diabetes, hypertension, smoking, and obesity were significant risk factors, and diabetes and smoking were reported to be significant risks in studies by Budoff et al (11) and Blaha et al (19). Uretsky et al (18) reported that the male gender, age, and smoking were risk factors, whereas Ueda et al (20) reported that diabetes and hypercholesterolemia were risk factors. Ergün et al (13) reported that age and diabetes were risk factors for both genders, whereas dyslipidemia was a risk factor for male patients, and family history was a risk factor for female patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the updated report by Uretsky et al [63], these soft plaques were rarely associated with hemodynamically significant stenosis and were associated with excellent prognosis. In addition, in the intermediate risk group, zero CACS was reported to exclude inducible ischemia in myocardial perfusion PET/CT [64].…”
Section: Validation Of Cacsmentioning
confidence: 99%